Book Review: 'Connecting in college: How friendship networks matter for academic and social success' by J. M. McCabe - Kenty-Drane, Jessica L. (American Journal of Sociology, 2018)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000434407000030 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.soc; peer-reviewed

Early Isolation: Racial and Economic Segregation in U.S. Public Elementary Schools - Kenty-Drane, Jessica L. (Race, Gender & Class, 2009)
The literature shows that racially and economically segregated schools diminish educational outcomes for students in non white schools with impoverished peers (Frankenberg & Lee, 2002; Mayer, 2000). To reveal which children are apt to begin their education in high minority and poor schools, this study drew on nationally representative data from the Early Childhood Longitudinal Study. Evidence documents variations in school racial and economic contexts according to children's race and social class backgrounds. Over half of Black and Hispanic first-graders attend segregated minority and poor schools while very few White first-graders do so. Additional analyses reveal that while social class is a useful predictor of educational segregation, it is less predictive for Black and Asian students than for White and Hispanic students.
Keywords: dept.soc; ⛔ No DOI found

Principles of racial integration vs. perceptions of non-White neighborhoods: Comparing hypothetical and real neighborhood choice - Meyerhoffer, Cassi A.; Kenty-Drane, Jessica (Journal of Urban Affairs, 2019)
Using qualitative interview data, we examine the consistency of White residents' responses to questions about their preferences for the racial composition of their neighborhoods when comparing hypothetical showcards and maps of real neighborhoods in respondents' cities. This approach allows for an examination of how residents' preferences for real neighborhoods align with preferences for idealized neighborhoods and the explanations people give when describing their preferences for neighborhoods of color. Data come from qualitative interviews conducted in Buffalo, New York, and Ogden, Utah.
3 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481781200007, lens.org/130-645-906-313-241 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: Buffalo; New York [New York (STT)]; New York [United States]; Ogden; United States; Utah; data set; dept.soc; neighborhood; peer-reviewed; perception; qualitative analysis; racial disparity; racial segregation

Wealth and education - Kenty-Drane, Jessica L. (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Google-Books-ID: xw5zAwAAQBAJ
Keywords: dept.soc

The yoke of childhood - Misgivings about children's relationship to technology in contemporary science fiction - Kenty-Drane, Jessica L. (Child and youth agency in science fiction: travel, technology, time, 2019)
Keywords: dept.soc; faculty_collection

Juvenile delinquency - Kenty-Drane, Jessica L. (Men and masculinities: a social, cultural, and historical encyclopedia, 2004)
This reference analyzes, summarizes, and explains the complexities of men's lives and the idea of modern manhood. It looks at literature, art, and music from a gender perspective, and covers intimacy, sexual violence, pornography, sexism and rituals.
OCLC: 301173623
Keywords: dept.soc

Connecticut - Kenty-Drane, Jessica L.; Prince-Stewart, Jamilah (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Google-Books-ID: xw5zAwAAQBAJ
Keywords: dept.soc

The racial wealth gap - Shapiro, Thomas M.; Kenty-Drane, Jessica L. (African Americans in the U.S. Economy, 2005)
Over the last several decades, academic discourse on racial inequality has focused primarily on political and social issues with significantly less attention on the complex interplay between race and economics. African Americans in the U.S. Economy represents a contribution to recent scholarship that seeks to lessen this imbalance. This book builds upon, and significantly extends, the principles, terminology, and methods of standard economics and black political economy. Influenced by path-breaking studies presented in several scholarly economic journals, this volume is designed to provide a political-economic analysis of the past and present economic status of African Americans. The chapters in this volume represent the work of some of the nation's most distinguished scholars on the various topics presented. The individual chapters cover several well-defined areas, including black employment and unemployment, labor market discrimination, black entrepreneurship, racial economic inequality, urban revitalization, and black economic development. The book is written in a style free of the technical jargon that characterizes most economics textbooks. While the book is methodologically sophisticated, it is accessible to a wide range of students and the general public and will appeal to academicians and practitioners alike.
Google-Books-ID: itUWFxWk4OYC
Keywords: Social Science / Ethnic Studies / African American Studies; dept.soc